ANALYSIS OF GAME IMPLEMENTATION IN TRAINING CONCENTRATION to ACHIEVE INTERPROFESSIONALISM - St. Mutrifatul Imthiatiyyah (Indonesian Journal of Health Care Management, 2023)
Interprofessional refers to collaboration and cooperation between professionals from different disciplines or fields to achieve a common goal. Concentration is a person's ability to focus attention on selected stimuli within a certain time. In order to improve concentration skills, specially created outbound activities with a focus in concentration are needed. The method used in writing this article is the literature review method. From the articles that have been reviewed, concentration training can be done with several things such as through games, sports and group guidance services. The ability to concentrate well can help ensure that professionals can work together effectively and efficiently.